Characteristic of semi refined and refined carrageenan flours used in the making of biofilm (bioplastic). Issue 1 (April 2021) - Wullandari, P; Sedayu, B B; Novianto, T D; Prasetyo, A W
Abstract: The physical, microbiological, and thermal properties of the raw material, semi refined and refined carrageenan derived from Eucheuma cottonii, were performed in purpose of preliminary research for biofilms (bioplastics) production. The physical properties i.e. particle size, pH, water content, gel strength and viscosity were tested. Meanwhile, the microbiological analysis were performed for the Total Plate Count, mold, and yeast. The thermal properties were performed using Differential Scanning Calorimetry (DSC). The results showed that the Semi Refined Carrageenan (SRC) and Refined Carrageenan (RC) flour have respectively a 60 and 80 mesh of particle size, an 8 and 7 of pH, a 7.9 and 8 % of the moisture content, a 560 and 1140 g / cm 2 of gel strength, and an 80 and 35 mPa·s of viscosity. The overall results of the microbiological tested showed that the SRC and RC were recognized as safe to be used for food application in accordance to the regulation, and the thermal analysis showed that the melting points of SRC and RC flour were respectively 168°C and 175°C.